2007
DOI: 10.1007/s00586-007-0451-6
|View full text |Cite
|
Sign up to set email alerts
|

Fusion and failure following anterior cervical plating with dynamic or rigid plates: 6-months results of a multi-centric, prospective, randomized, controlled study

Abstract: Anterior cervical plate fixation is an approved surgical technique for cervical spine stabilization in the presence of anterior cervical instability. Rigid plate design with screws rigidly locked to the plate is widely used and is thought to provide a better fixation for the treated spinal segment than a dynamic design in which the screws may slide when the graft is settling. Recent biomechanical studies showed that dynamic anterior plates provide a better graft loading possibly leading to accelerated spinal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 22 publications
2
32
0
2
Order By: Relevance
“…Surgeons also prefer to add an anterior plate to enhance rigidity of fixation especially in multi-level cases (11,23,24). Although the design of the current anterior plate has been improved over the years, the complications related to the plates are still not rare, and include screw loosening or breakage, plate breakage, and screw pullout with or without migration into the gastrointestinal tract (15,25).…”
Section: █ Resultsmentioning
confidence: 99%
“…Surgeons also prefer to add an anterior plate to enhance rigidity of fixation especially in multi-level cases (11,23,24). Although the design of the current anterior plate has been improved over the years, the complications related to the plates are still not rare, and include screw loosening or breakage, plate breakage, and screw pullout with or without migration into the gastrointestinal tract (15,25).…”
Section: █ Resultsmentioning
confidence: 99%
“…This study was scored Class III because of unblinded outcome observation, lack of reliability testing for the questionnaire, and the fact that any patients lost to follow-up were replaced. 30 Stulik et al 32 reported on 132 patients who underwent dynamic (69 patients) or rigid (63 patients) plate fixation for 1-or 2-level cervical surgery. The authors used dynamic radiographs to assess instability at 3 and 6 months postoperatively.…”
Section: Rigid Versus Dynamic Fixationmentioning
confidence: 99%
“…This study was scored Class III because of poor follow-up (58%) and lack of details on randomization or allocation concealment. 32 …”
Section: Rigid Versus Dynamic Fixationmentioning
confidence: 99%
“…The surgical outcomes with the anterior plate technique are acceptable, but various hardware-related complications have been reported, including oblique plate, migration of the plate, and/or back out of screws, in more than 30% of cases. 1,[4][5][6]8) One of the most serious complications of hardware failure is esophageal violation. 2,3,6,7) The implanted hardware should be removed after confirmation of solid bone fusion, but compliance seems to be low because of complications caused by reoperation through the anterior approach.…”
Section: Introductionmentioning
confidence: 99%